2008
DOI: 10.1152/ajpendo.90288.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia prevents the suppressive effect of hyperinsulinemia on plasma adiponectin levels in healthy humans

Abstract: Blü mer RM, van der Crabben SN, Stegenga ME, Tanck MW, Ackermans MT, Endert E, van der Poll T, Sauerwein HP. Hyperglycemia prevents the suppressive effect of hyperinsulinemia on plasma adiponectin levels in healthy humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…The small sample size, with a trend for slightly different baseline characteristics, particularly concerning the severity of the shock, as well as the nonblinded nature of the study, however, may have played a confounding role. Nevertheless, if the increase in forearm flow is indeed evoked by the more intensive insulin therapy, it corroborates extensive data from basic research in in vitro cellular models [2-4] and from in vivo animal research [5,6], as well as observations in healthy subjects [7,8] and on tissue samples obtained from patients in the proof-of-concept study on blood glucose control performed in Leuven [9,10]. Together, these previous data suggested that insulin signaling mediates a direct and/or indirect protection of the endothelium and the cardiovascular system, but that this is antagonized by concomitant pronounced hyperglycemia.…”
supporting
confidence: 80%
“…The small sample size, with a trend for slightly different baseline characteristics, particularly concerning the severity of the shock, as well as the nonblinded nature of the study, however, may have played a confounding role. Nevertheless, if the increase in forearm flow is indeed evoked by the more intensive insulin therapy, it corroborates extensive data from basic research in in vitro cellular models [2-4] and from in vivo animal research [5,6], as well as observations in healthy subjects [7,8] and on tissue samples obtained from patients in the proof-of-concept study on blood glucose control performed in Leuven [9,10]. Together, these previous data suggested that insulin signaling mediates a direct and/or indirect protection of the endothelium and the cardiovascular system, but that this is antagonized by concomitant pronounced hyperglycemia.…”
supporting
confidence: 80%
“…The decrease of total plasma adiponectin concentrations in the control group during hyperinsulinemia is a known phenomenon (15). Although the change in plasma adiponectin levels did not differ between the LPS and the control group, the blunted decrease in adiponectin upon insulin infusion after administration of LPS may contribute to the higher Rd and the lower EGP in this group.…”
Section: Discussionmentioning
confidence: 73%
“…The present study was part of a study on the differential effects of plasma glucose and insulin concentrations on several parameters relevant for critically ill patients (12)(13)(14)(15). The data on glucose metabolism, measured with stable isotopes in the present study, have not been published earlier.…”
Section: Protocolmentioning
confidence: 99%
“…Importantly, contradictory reports concerning the effect of insulin on adiponectin multimers have been published. Selective decreases in HMW [11] as well as no changes in circulating concentrations of this isoforms [15] were reported. A possible explanation for the lack of insulin effect on adiponectin concentrations is that the inhibitory effect of insulin on adiponectin is not dose depended.…”
Section: Discussionmentioning
confidence: 99%